GIS-material for the archaeological project: Five archaeological investigations on the plains of western Östergötland_4 - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the Swedish Rail Administration's plans of extending the railway between Motala and Mjölby, by construction of double-tracks and levelled crossings, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, has performed several excavations along the railway during the years of 2003-2005. Five separate sites were investigated, together forming the Fågelsta Project, a part of the overall project "The Plain Region - western Östergötland in a long term perspective". The archaeological remains consisted of Neolithic and Pre-Roman Iron Age settlements, furnaces from the transition between the Bronze and Iron Age, graves and a cult building from the Vendel period and the Viking Age and a medieval road (beside RAÄ 21, 27, Västra Stenby parish); abandoned fields from the transition between the Bronze and Iron Age, Late Iron Age settlement, Early Medieval features and a smithy from the Modern Era (RAÄ 225, Västra Stenby parish); settlement remains and stray finds from the Stone Age to the Early Iron Age (beside RAÄ 14-19, Västra Stenby parish); settlement remains from the Early and Late Neolithic, Bronze Age, the transition between the Bronze and Iron Age, the Roman Iron Age, and Vendel period/Viking age, possible village formation (beside RAÄ 32, Fivelstad parish) and finally Neolithic and Bronze Age settlement remains, abandoned fields from the Bronze Age and the Pre-Roman Iron Age, and a Pre-Roman workshop area (beside RAÄ 26, Fivelstad parish). A total of 23 300 m2 was investigated.

Purpose:

The information in the purpose is translated from the archaeological report:
The main theme of the Fågelsta Project was "People of the plains - settlement changes in a long term perspective". The aim was to describe the landscape development in the area from a comprehensive point of view. This aim was then divided into four sub-themes; Continuity and transitions, Land use in a local perspective, Settlement and settlement structure and Central places and areas. The aim was also to relate the prehistoric development and land use in west Östergötland to the neighbouring regions.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har med anledning av Banverkets planering för utbyggnad till dubbelspår av järnvägssträckningen mellan Motala och Mjölby och därtill anslutande planskilda korsningar utfört särskilda arkeologiska undersökningar längs med sträckan under åren 2003-2005. Undersökningarna ägde rum inom sammanlagt fem skilda lokaler som tillsammans utgjorde delprojektet Fågelstaprojektet, inom det övergripande linjeprojektet Slättbygdsprojektet - västra Östergötland i ett långtidsperspektiv. Lämningarna utgjordes av neolitiska och förromerska boplatslämningar, gropschaktugnar från övergången mellan brons- och järnålder, gravar och kultbyggnad från vendel- och vikingatid samt en medeltida vägsträckning (Landstorp, invid RAÄ 21, 27, Västra Stenby socken); fossil åkermark från övergången bronsålder - järnålder, boplats från yngre järnålder, tidigmedeltida anläggningar och smedja från historisk tid (Fågelstads by, RAÄ 225, Västra Stenby socken); boplatslämningar och lösfynd från stenålder - äldre järnålder, bl a en stor boplats från äldre järnålder (Hallingstorp, invid RAÄ 14-19, Västra Stenby socken); boplatser och boplatslämningar från tidigneolitikum, senneolitikum, bronsålder, övergången brons- och järnålder respektive romersk tid samt vendel/vikingatida hus, eventuellt tidig byetablering? (Sund, invid RAÄ 32, Fivelstad socken) och slutligen boplatslämningar från neolitisk tid och bronsålderboplats, fossil åkermark från bronsålder respektive förromersk järnålder samt förromerskt aktivitets- eller hantverksområde (Russingstorp, invid RAÄ 26, Fivelstad socken). Sammanlagt undersöktes ca 23 300 m2.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
För Fågelstaprojektet formulerades initialt ett övergripande tema: Slättbygdens människor - bebyggelseförändringar i ett långtidsperspektiv. Den övergripande målsättningen var att betrakta landskapsutvecklingen i området ur ett helhetsperspektiv. Den övergripande målsättningen bröts i sin tur ned i fyra underteman med tillhörande frågeställningar: Kontinuitet och brytningstider, Lokalisering och markutnyttjande i ett lokalt perspektiv, Bebyggelse och boplatsstruktur samt Centrala platser och centrala områden. Avsikten är också att ställa bilden av den förhistoriska utvecklingen och resursutnyttjandet i västra Östergötland i relation till de centrala och östra delarna av Östergötland samt till andra närliggande regioner.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Fem arkeologiska undersökningar i västra Östergötlands slättbygd_4
Fågelstaprojektet
Keywords: stone age; stenålder; Late Neolithic; senneolitikum; Bronze Age; bronsålder; Iron Age; järnålder; Roman Iron Age; romersk järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi